Pediatric antibiotic stewardship programs in Europe: a pilot survey among delegates of The European Academy of Pediatrics - Stephen M. Reingold; Zachi Grossman; Zachi Grossman; Adamos Hadjipanayis; Adamos Hadjipanayis; Stefano Del Torso; Arunas Valiulis; Arunas Valiulis; Lukasz Dembinski; Shai Ashkenazi (Frontiers Media S.A., 2023)
BackgroundAntimicrobial resistance (AMR) is one of the leading causes of morbidity and mortality worldwide. Efforts to promote the judicious use of antibiotics and contain AMR are a priority of several medical organizations, including the WHO. One effective way to achieve this goal is the deployment of antibiotic stewardship programs (ASPs). This study aimed to survey the current situation of pediatric ASPs in European countries and establish a baseline for future attempts to harmonize pediatric ASPs and antibiotic use in Europe.MethodsA web-based survey was conducted among national delegates of the European Academy of Paediatrics (EAP). The survey assessed the presence of pediatric ASPs in the representatives' countries in the inpatient and outpatient settings, the staff included in the programs, and their detailed activities regarding antibiotic use.ResultsOf the 41 EAP delegates surveyed, 27 (66%) responded. Inpatient pediatric ASPs were reported in 74% (20/27) countries, and outpatient programs in 48% (13/27), with considerable variability in their composition and activities. Guidelines for managing pediatric infectious diseases were available in nearly all countries (96%), with those for neonatal infections (96%), pneumonia (93%), urinary tract (89%), peri-operative (82%), and soft tissue (70%) infections being the most common. Pediatric ASPs were reported at the national (63%), institutional (41%), and regional/local (<15%) levels. Pediatricians with infectious disease training (62%) and microbiologists (58%) were the most common members of the program personnel, followed by physician leaders (46%), infectious disease/infection control physicians (39%), pharmacists (31%), and medical director representatives (15%). Activities of the pediatric ASPs included educational programs (85%), monitoring and reporting of antibiotic use (70%) and resistance (67%), periodic audits with feedback (44%), prior approval (44%), and post-prescription review of selected antibiotic agents (33%).ConclusionAlthough pediatric ASPs exist in most European countries, their composition and activities vary considerably across countries. Initiatives to harmonize comprehensive pediatric ASPs across Europe are needed.